The Use of Barometers in Forecasting Changes in the Banking Market Situation - Garczarczyk, Józef; Skikiewicz, Robert (Zastosowanie barometrów koniunktury w przewidywaniu zmian sytuacji na rynku bankowym, 2010)
Barometers, constructed for almost a century as composite indicators on the basis of variables which exhibit leading features, are commonly used to determine the direction of the future changes in the whole economy or its sectors. In relation to the immense importance of the banking sector for the functioning of the whole economy, the forecasting of the changes in the banking market assumes a particular importance. The barometers presented in the article constructed for two most important elements from the banking market, namely PLN deposits and PLN loans allow for accurate forecasting of the occurrence of the turning points in the business cycle. Composite leading indicators constructed for both referential variables maintained, in a majority of cases, good forecasting characteristics and signalled almost all turning points in the cycle of PLN loans and PLN deposits. This confirms the usefulness of the method applied for forecasting the development of the market of banking services.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 43-58
Keywords: barometers; composite leading indicators; forecasting; banking market